Upaya Meningkatkan Hasil Belajar pada Materi Berbahasa Krama Inggil Menggunakan Metode Bermain Peran dengan Model Pembelajaran Cooperative Learning - SM Ningrum (Universitas Muhammadiyah Enrekang, 2022)
Class action research in general aims to improve the quality of learning for students of grade IV Purwoprajan II State Elementary School. Specifically aimed at: (1) Describe the activities of learners; (2) Describe the management of learning by the teacher; (3) Knowing the learning outcomes of learners who refer to role-playing methods with cooperative learning models in grade IV of Purwoprajan II State Elementary School even semester of the 2019/ 2020 school year for Javanese mulok subjects on krama inggil language material. Study subjects grade IV SDN Purwoprajan II Jebres Surakarta. Research data is obtained by observation and documentation. Then analyzed with descriptive qualitative. Research is conducted in two cycles in which each cycle consists of stages of planning, implementation, observation, and reflection. The results of the study concluded that the use of role-playing methods with cooperative learning models can increase the increase in the average value of learners in learning the language material in Javanese language content.